Application Of Organic Fertilizer Raw Materials Of Chromolaena odorata And Mycorrhizal Fungi On Local Corn Plant In Sub-Optimal Land) - Andi Nurmas; Rachmawati Hasid; Miki Prawati; Makmur Jaya Arma; Robiatul Adawiyah (Journal of Tropical Mycorrhiza, 2023)
. Application of organic fertilizer raw materials Chromolaena odorata and mycorrhizal fungi is one solution to improve the physical, chemical and biological soil at sub-optimal land and reduce environmental pollution due to excessive use of inorganic fertilizers on the local corn plant. The aim of  study was to evaluated the role of bokashi C.odorata and mycorrhizal fungi in improving the growth and production of local corn. The research design used was a factorial randomized block design (RBD), consisting of two     factors. First factor was the dose of bokashi fertilizer (C), consisting of 4 treatment levels, namely: 0; 2; 4 and 6 t ha-1. Second factor was mycorrhizal fungi (F) inoculation, consisting of 3 treatment levels, namely, 25; 50 and 75 g planting holes-1. Bokasi fertilizer C.odorata and mycorrhizal fungi were significant on growth and production variables, such as: plant height (cm), leaf area index (cm2), RGR (g..g-1.day-1), dry weight of corn cobs (g), and dry seed production (ton ha-1). The Result of combination bokashi fertilizer C.odorata (6 tons ha-1) and mycorrhizal fungi (50 g planting hole-1) was the best treatment with obtained Konawe local dried corn production of 4.48 tons ha-1.